A Systematic Review of Librarian-Provided Services Delivered in Healthcare Settings Finds a Positive Effect on Clinician and Patient Relevant Outcomes and Identifies Gaps in the Evidence - Stovold, Elizabeth Margaret (Evidence Based Library and Information Practice, 2015)
A Review of: Perrier, L., Farrell, A., Ayala, A. P., Lightfoot, D., Kenny, T., Aaronson, E., . . . Weiss, A. ( 2014). Effects of librarian-provided services in healthcare settings: A systematic review. Journal of the American Medical Informatics Association, 21(6), 1118-1124. http://dx.doi.org/10.1136/amiajnl-2014-002825 Abstract Objective – To assess the effects of librarian-provided services, in any healthcare setting, on outcomes important to patients, healthcare providers, and researchers. Design – Systematic review and narrative synthesis. Setting – MEDLINE, CINAHL, ERIC, LISA, and CENTRAL databases; library-related websites, conference proceedings, and reference lists of included studies. Subjects – Twenty-five studies identified through a systematic literature search. Methods – In consultation with the review team, a librarian designed a search to be run in MEDLINE that was peer-reviewed against a published checklist. The team then conducted searches in the five identified databases, adapting the search as appropriate for each database. Authors also checked the websites of library and evidence based healthcare organisations, along with abstracts of relevant conference proceedings, to supplement the electronic search. Two authors screened the literature search results for eligible studies, and reached agreement by consensus. Studies of any librarian-delivered service in a healthcare setting, directed at either patients, clinicians of any type, researchers, or students, along with studies reporting outcomes relevant to clinicians, patients, or researchers, were eligible for inclusion. The authors assessed results initially on the titles and abstracts, and then on the full-text of potentially relevant reports. The data from included studies were then extracted into a piloted data extraction form, and each study was assessed for quality using the Cochrane EPOC risk of bias tool or the Newcastle-Ottawa scale. The results were synthesised narratively. Main Results – The searches retrieved a total of 25 studies that met the inclusion criteria, comprised of 22 primary papers and 3 companion reports. Authors identified 12 randomised trials, 4 controlled before-and-after studies, 3 cohorts, 2 non-randomised trials, and 1 case-control study. They identified three main categories of intervention: librarians teaching search skills; providing literature searching as a service; and a combination of the teaching and provision of search services. The interventions were delivered to a mix of trainees, clinicians, and students. None of the studies examined services delivered directly to patients or to researchers. The quality assessment found most of the studies had a mid- to high-risk of bias due to factors such as lack of random sequence generation, a lack of validated tools for data collection, or a lack of statistical analysis included in the study. Two studies measured patient relevant outcomes and reported that searches provided by librarians to clinicians had a positive impact on the patient’s length of stay in hospital. Five studies examined the effect of librarian provided services on outcomes important to clinicians, such as whether a literature search influenced a clinical decision. There was a trend towards a positive effect, although two studies found no significant difference. The majority of studies investigated the impact of training delivered to trainees and students on their literature search skills. Twelve of these studies found a positive effect of training on the recipients’ search skills, while three found no difference. The secondary outcomes considered by this review were satisfaction with the service (8 studies), relevance of the answers provided by librarians (2), and cost (3). The majority reported good satisfaction, and relevance. A cost benefit was found in 2 of 3 studies that reported this outcome. Conclusion – Authors report a positive effect of training on the literature search skills of trainees and students, and identified a benefit in the small number of studies that examined librarian services to clinicians. Future studies should use validated data collection tools, and further research should be conducted in the area of services provided to clinicians. Research is needed on the effect of librarian-provided services to patients and researchers as no studies meeting the inclusion criteria examining these two groups were identified by the literature search.